Uji Aktivitas Ekstrak Etanol Daun Dadap Serep (Erythrina lithosperma Miq) sebagai Antibakteri terhadap Bakteri Salmonella typhi - Andi Noor Kholidha; I Putu Wira Putra Suherman; Hartati Hartati (Halu Oleo University, 2016)
Dadap serep (Erythrina lithosperma Miq) is one of the plants that grow in Indonesia. Dadap serep leaves are commonly used as a traditional medicin. It can be used as an antimicrobial. This study aims to determine the inhibition of Dadap Serep (Erythrina lithosperma Miq) Leaf Extract on the growth of the bacteria Salmonella typhi. The methods used in this research was an analytic experimental test. The samples of this study are Leaf Extract of Dadap Serep (Erythrina lithosperma Miq), which is divided into eight concentration, i.e. the concentration of 200,000 ppm, 100,000 ppm, 50,000 ppm, 25,000 ppm, 12,500 ppm, 6,250 ppm, 3,125 ppm, 1,560 ppm and two control i.e. a positive controls and a negative controls. Each test was repeated three times. Antibacterial activity test performed by disc diffusion method, wherein the diameter of each extract was determined and assessed their effectiveness inhibitory zone with chloramphenicol. Minimum Inhibitory Concentration (MIC) was determined by disc diffusion method togeth er with the inhibition test. We then measured at the lowest concentration of extract that they can inhibit the bacteria Salmonella typhiTop of FormBottom of Form. The results showed that the leaves of Dadap Serep (Erythrina lithosperma Miq) has antibacterial activity against growth of bacteria Salmonella typhi. MIC seen from the leaves of Dadap Serep is 50,000 ppm with inhibition zone diameter of 1.3 mm were formed. Diameter of clear zone is highest at a concentration of 200,000 ppm with inhibition zone diameter formed is 4.83 mm. Phytochemical test results on Leaf of Dadap Serep (Erythrina lithosperma Miq) retrieved alkaloids, flavonoids, tannins and saponins are positive.From this research it can be concluded that the extracts from dadap serep leaves (Erythrina lithosperma Miq) has antibacterial activity against growth of bacteria Salmonella typhi.Keywords: Dadap serep leaves (Erythrina lithosperma Miq), Salmonella typhi, Minimum inhibitory concentration (MIC), Antibacterial test